Relationship between School Culture and Work Motivation in Vocational High Schools - Putri Anandita; Anisah Anisah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
The research is based on the results of the author's observations showing that the teacher's motivation is not optimal. Therefore, many factors affect work motivation, one of which is organizational culture. The purpose of the study was to determine: 1) work motivation, 2) school culture and 3) the relationship between organizational culture and work motivation. The hypothesis of the research is "there is a significant relationship between school culture and work motivation". This type of research is correlational. The population consists of all teachers who are in SMK totaling 63 people and also the sample of this study. The research instrument is a Likert Scale model with five alternative answers that have been tested for validity and reliability using the SPSS application. Data analysis using the Product Moment correlation formula. The results showed that 1) school culture was in the good category with a score of 87.6%, 2) work motivation was in the very high category with a score of 90.2%, and 3) there was a significant relationship between school culture and teacher work motivation of 0.450 which belongs to the moderately correlated